The Role of Specific Mitogen-Activated Protein Kinase Signaling Cascades in the Regulation of Steroidogenesis. (5th January 2011) - Manna, Pulak R.; Stocco, Douglas M.
Abstract : Mitogen-activated protein kinases (MAPKs) comprise a family of serine/threonine kinases that are activated by a large variety of extracellular stimuli and play integral roles in controlling many cellular processes, from the cell surface to the nucleus. The MAPK family includes four distinct MAPK cascades, that is, extracellular signal-regulated kinase 1/2 (ERK1/2), p38 MAPK, c-Jun N-terminal kinase or stress-activated protein kinase, and ERK5. These MAPKs are essentially operated through three-tiered consecutive phosphorylation events catalyzed by a MAPK kinase kinase, a MAPK kinase, and a MAPK. MAPKs lie in protein kinase cascades. The MAPK signaling pathways have been demonstrated to be associated with events regulating the expression of the steroidogenic acute regulatory protein (StAR) and steroidogenesis in steroidogenic tissues. However, it has become clear that the regulation of MAPK-dependent StAR expression and steroid synthesis is a complex process and is context dependent. This paper summarizes the current level of understanding concerning the roles of the MAPK signaling cascades in the regulation of StAR expression and steroidogenesis in different steroidogenic cell models.